2016
DOI: 10.1155/2016/6197961
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Revised Curriculum Focusing on Clinical Neurology and Musculoskeletal Care on a Required Fourth-Year Medical Student Physical Medicine and Rehabilitation Clerkship

Abstract: Background. A Required Fourth-Year Medical Student Physical Medicine and Rehabilitation (PM&R) Clerkship was found to increase students' knowledge of PM&R; however the students' overall rotation evaluations were consistently lower than the other 8 required clerkships at the medical school. Objective. To describe the impact of a revised curriculum based upon Entrustable Professional Activities and focusing on basic pain management, musculoskeletal care, and neurology. Setting. Academic Medical Center. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…[3][4][5][6][7][8][9] There are various levels of familiarity and attitude toward the different areas of PM&R; however, the field as a whole is becoming more well-known as medical students start to recognize the value of physiatric skillsets in enhancing their understanding of how to comprehensively evaluate, diagnose, and treat a wide range of pathologies. [10][11][12][13] A prior 16-item, 130-factor questionnaire administered to graduating PM&R residents by DeLisa et al found that some of the most popular factors influencing resident decisions for residency programs included: "flexibility for family obligations, opportunities to make a difference in peopleʼs lives, interest in helping people, type of patient problem encountered, and consistency with the personality." 14 Given the increasing popularity of PM&R and a lack of a dedicated study evaluating the PM&R residency websites and online content, we found a need to further address this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] There are various levels of familiarity and attitude toward the different areas of PM&R; however, the field as a whole is becoming more well-known as medical students start to recognize the value of physiatric skillsets in enhancing their understanding of how to comprehensively evaluate, diagnose, and treat a wide range of pathologies. [10][11][12][13] A prior 16-item, 130-factor questionnaire administered to graduating PM&R residents by DeLisa et al found that some of the most popular factors influencing resident decisions for residency programs included: "flexibility for family obligations, opportunities to make a difference in peopleʼs lives, interest in helping people, type of patient problem encountered, and consistency with the personality." 14 Given the increasing popularity of PM&R and a lack of a dedicated study evaluating the PM&R residency websites and online content, we found a need to further address this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinally integrated clerkship structures appeared to be better suited for meaningfully collecting several entrustment data points for high-stakes entrustment decisions over time [ 18 , 29 , 30 , 33 , 37 ]. Traditional block clerkship curricula ranging from two to 12 weeks were, however, the predominant structure in the EPA-based clerkship curricula [ 20 , 22 27 , 32 , 36 , 38 44 ]. Two articles reported highly integrated, and longitudinally and specialty oriented, EPA-based curricula that covered both UME and GME, one in pediatrics [ 35 ] and one in internal medicine [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Simulation that is aligned with sound educational principles and theory and provides an authentic opportunity for practice and feedback on performance has been shown to be effective in facilitating the development of clinical competency and satisfaction of learners [5,6]. Because of such evidence, we have implemented simulation-based opportunities for our learners to develop skill in MSK physical examination and clinical reasoning in the orthopaedic clinical clerkship rotation in our university hospital.…”
Section: Introductionmentioning
confidence: 99%